Penerapan Model Discovery Learning Dalam Upaya Meningkatkan Kemampuan Pemahaman Matematis Dan Pemecahan Masalah Matematis - Mugni, Abdul; Turmudzi, Didi; G. Kartasasmita, Bana (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2021)
The research of mix method with the type of embedded design is aimed to know the improvement and the difference of the improvement of mathematical understanding ability and mathematical problem solving ability among the students who get the discovery learning model with the students who get the conventional learning. The population in this study is all students of class VII MTs Persis Pasirwangi with two classes of samples, namely: class VII-C using discovery learning model and class VII-D using conventional learning. Instruments used in research: mathematical comprehension ability test and mathematical problem solving ability. From result of research analysis obtained: 1). There is no difference in the improvement of students' mathematical understanding among students who get discovery learning model with students who get conventional learning, 2). There is a difference in the ability of students to solve mathematical problems between students who get discovery learning model with students who get conventional learning in terms of KAM (High, Medium, and Low), 3) .Effect size of learning discovery learning to improve understanding ability and problem solving ability mathematically fall into the category of being.